(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Clinical characteristics, histological structure, and surgical technique of persisting pupillary membrane (PPM) have been presented in the modern literature in insufficient and, in some cases, contradictory reports. Purpose. To describe clinical characteristics and histological structure of PPM, as well as PPM surgery for restoring the transparency of the optic axis and eliminating anisometropia through refractive lens exchange. Material and Methods. Complete ophthalmic examination including ultrasound biometry and scanning followed by surgical removal of PPM and refractive exchange of the clear lens was performed in an 11-year-old patient with high myopia, anisometropia and myopia Results. The PPM case reported is a combination of multiple strands, aligning with the iris in color, involved in the stroma and the inner half of the iris and attached to the anterior lens. The strands, thus, obscured 2/3 of the iris. By sequential surgical dissection of the PPM strands, the membrane was detached from the anterior capsule and removed from the eye. Refractive lens exchange was performed using a standard technique. Histological studies showed a dual character of the removed PPM: the presence of both thick fibrous connective tissue and loose fibrous tissue, resembling the stroma of the iris with the presence of collapsed capillaries. Conclusions. 1. The rare clinical case described is an example of combined type 1 and type 2 PPM according to Duke-Elder’s classification (1964) or a combination of accessory iris membrane and persistant pupilеae membrane. With the point of Duke-Elder’s classification, this membrane can be considered a special variant of type 2 PPM whereas there is no connection with the lens capsule. 2. Attachement of PPM to the anterior lens capsule, which seemed quite tight, was false since PPM, after being dissected, spontaneously detached from the lens with the latter preserved intact and transparent, which contributed to recover the transparency of the optic axis. 3. One-stage refractive replacement of the lens made it possible to eliminate high myopia and high anisometropia, which made it possible to increase visual acuity of the eye and to create maximal favorable conditions for amblyopia treatment that followed.